Spontaneous outbreak of Pascalia glauca poisoning in sheep in Argentina - Liboreiro, Matías; Flores Olivares, Carlos; Armendano, Joaquín Ignacio; Schild, Carlos; Fernandez, Eduardo Luján; Odriozola, Ernesto Raul; Morrell, Eleonora Lidia; Canton, German Jose (Brazilian Association of Veterinary Pathology, 2021)
Pascalia glauca is a native weed and one of the most common hepatotoxic plant affecting cattle in Argentina. Although experimental P. glauca poisoning have been reported in sheep, no spontaneous cases have been reported in this species. This work describes an outbreak of intoxication after spontaneous consumption of P. glauca, affecting 20% (6/30) sheep of a commercial flock. Affected sheep were ataxic, depressive, with mucous nasal discharge, cough and abdominal breathing. During post mortem examination, liver was swollen and a diffuse enhancement of the reticular pattern (“nutmeg liver”) was visible. Histopathological examination reveals severe and extensive acute diffuse centrilobular hepatic necrosis with hemorrhage. The presence of the toxic plant, the clinical and pathological findings allows us to confirm the etiology of this outbreak.